Distribution and Abundance of Black Band Disease on Corals Montipora sp in Seribu Islands, Jakarta - Johan, Ofri; Bengen, Dietriech G; Zamani, Neviaty P; _, Suharsono (Journal of Indonesian Coral Reefs, 2012)
Research on the abundance and distribution of coral disease has been implemented since June andJuly 2011 to determine the preliminary abundance of coral disease on several islands in the Thousand Islands, Jakarta. Observation method used was a 20m-belt transect with 1 m width to the left and right, and 3 replicates. Transects placed on the reef flat with a depth of 0Ã¢â¬â3 m, and a record number of infected colonies of BBD. The results show that type coral diseases of BBD found in many high coral covers and where Montipora sp dominant at that location. Generally, highest abundances found were at northern of Pramuka Island (0.15 col/m), eastern of Pari Island (0.092 col/m), Penjaliran Island (0.092 col/m), and Tikus Island (0.085 col/m). Statistical test by ANOVA obtained that abundance of BBD was significantly different between groups of study sites, i.e. the distance between the nearest and middle sites, and between the nearest and farthest distance from the mainland of Java Island (significantly difference with value respectively 0.030 and 0.025; confidence level 5%). Meanwhile, the sites between middle and farthest show no real difference. Based on climatological data, the increase in temperature in March and July could lead to coral diseases that occured in the Thousand Islands region.